Cultural Processes and Teacher-Educators’ Technology Knowledge and Skills at Makerere University - David Kakeeto; Anthony Muwagga Mugagga; Ronald Bisaso (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
The study was set out to examine the influence of cultural processes on teacher educators’ digital competence at School of Education, Makerere University, and Kampala Uganda. A case study design was employed taking a quantitative approach. Objectives of the study were to establish how individual and institutional values influence teacher educators’ technology knowledge and skills at Makerere University. Participants were teacher trainers from School of Education and data were collected using a self administered questionnaire. Data were analyzed using; ANOVA, Pearson Product moment Correlation coefficient and Regression. It was found out that: both individual and institutional values have got a significant positive influence to teacher educators’ technology knowledge and skills. It was concluded that; individual values in form of: level of education, teaching experience, attitude or belief and disciplinary background are very fundamental in promoting teacher educators’ technology skills and knowledge; institutional values in form of: leadership styles, policy guidelines, curriculum and structural facilities are critical aspects in promoting teacher educators’ technology knowledge and skills. It was recommended that The School of Education should develop an evaluative instrument to regularly assess the extent to which ICTs have promoted teaching and learning, University administrators should change their leadership styles, adopt transformational leadership style according because results indicated that it promotes teacher educators’ technology knowledge and skills